Pedro Calderón de la Barca : La Desdicha de la Voz. - Mason, T. R. A. (Hispanic Studies Textual Research and Criticism, 15., 2003)
This is a definitive critical edition of the holograph manuscript (1639) of Calderón?s comedy. This volume traces the textual history of the play and lists variants from all known editions printed in or immediately after Calderón?s lifetime; it also gives a brief account of editions printed up to the end of the eighteenth century. Two sets of notes are provided: one listing and discussing all the emendations, additions and deletions made by Calderón in the course of the composition of the play; and the other offering clarification of words and allusions in the text which might cause difficulty.